Effect of ultrasound pre-treatments before enzymatic hydrolysis on physicochemical, nutritional and functional properties of insoluble protein fractions obtained from Atlantic mackerel side streams - Janna Cropotova; Kristine Kvangarsnes; Elissavet Kotsoni; Revilija Mozuraityte; Inger Beate Standal; Amélie Le Gall; Turid Rustad (Bioresources and Bioprocessing)
Abstract This study investigated the impact of ultrasound (US) pre-treatment before enzymatic hydrolysis on physicochemical, nutritional, and functional properties of insoluble protein fractions obtained from fish side streams after filleting of Atlantic mackerel (heads, backbones, fins, tails and trimmings). Four fractions were analyzed: a control without US-treatment and US-treated samples at 300 W, 450 W, and 600 W. The results showed that ultrasonication significantly increased total protein content in insoluble protein fraction after the treatment at 300 W. Additionally, salt-soluble proteins increased significantly in 450 W and 600 W samples, while water-soluble proteins increased after US-treatment at 600 W, suggesting that higher US-intensities promoted protein bond breakdown and exposure of hydrophilic amino acid groups. The degree of hydrolysis increased significantly in 450 W sample due to cavitation effect of ultrasound. Total thiols decreased in water-soluble proteins after US-treatment at 300 W and 450 W, as well as in all salt-soluble proteins compared to control due to unfolding of proteins and breakage of disulfide bonds. No significant differences were detected in lipid oxidation markers (TBARS and ¹H NMR aldehyde profile). From the nutritional perspective, the nutritional indexes of lipid quality AI (atherogenicity index), TI (thrombogenicity index), and HH (hypocholesterolemic fatty acid ratio) were favorable for all insoluble protein fractions. US-treatment enhanced the hypocholesterolemic profile of insoluble protein fractions by lowering their HH index. P-NMR lipid profiling identified PC and PC-ether as the predominant phospholipids (70–74% of total PL content). No significant differences were found in color parameters (L, a, b*) between control and US-treated samples at 300 W and 450 W. Graphical abstract